Optimization of electrospinning parameters for producing silk fibroin/poly(ethylene oxide) nanofibers using D-optimal method - Mina Rajabi; Payam Zahedi; Zahra Hassannejad; Ismaeil Haririan (Journal of Natural Fibers, 2019)
Despite the ease of the electrospinning process of synthetic polymers, the adjustment of several independent variables for natural ones is a complex procedure. In this work, the electrospinning parameters of silk fibroin (SF)/poly(ethylene oxide) (PEO) blends including tip-to-collector distance (X1), applied voltage (X2), flow rate (X3) and SF/PEO ratio (X4) were optimized using the D-optimal method. By considering the response surface plots and interaction graphs as well as observing the scanning electron microscopy (SEM) images, the optimized conditions were set as follows: X1 = 15 cm, X2 = 12 kV, X3 = 1.2 mL/h and X4 = 4. Accordingly, the electrospun SF/PEO nanofibrous sample with uniform morphology and an average diameter of 182 ± 55 nm was obtained.